The Evaluation of Implementation of Regional Policy in Acceding Countries of European Union - Simanavičienė, Žaneta; Kilijonienė, Akvilė (Ekonomika, 2004)
The essence of the article is to present the main theoretical aspects of regional policy and aspects concerning the process of formation and realization of the aims and goals the regional policy pursues. The article focuses on working out an effective evaluation method, which could be applied to achieve reliable results and could he effective in solving problems of regional development. The article discusses all possible ways of problem solving of regional policy. There is a lot of controversy over the notion regional policy. The fact that scientists have not settled their arguments over the notion is a clear indication that the issue is important in many poor or even developed countries. We should speak about regional policy in case the government patronizes certain regions while other regions are in a state of neglect. A country suffering from depression prefers regional policy, which is oriented to economical development, that is, the growth of economy. Once a certain level of the growth in economy has been achieved, the priority becomes elimination of differences in the regions. The aims and goals of regional policy could be grouped by two criterions: regional solidity and regional oneness. The aims and goals of regional policy have been changed in many countries and serve as the means of economic development of the whole country. This policy is implemented in virtue of two strategies of regional development - the one is oriented to encourage the growth of economy, and the other targets elimination of regional differences in the country. The main strategy of regional development is to establish institutions, change financial infrastructure and implement the regional policy, which would guarantee permanent and balanced development. Methodology of evaluation of implementation of regional policy is principal and in all cases reliant on national initiatives or role of government policy. The realization of regional policy largely is depended of local and regional initiatives, which are responsible for protection of resources and promotion of variety, i.e. expansion of attraction of territory. There are 3 steps in evaluating regional policy: the evaluation of the social - economic situation, the identification of the weak and strong points in the region as well as prospects of the means of the government’s policy. There are two ways how to stimulate regional development: direct and indirect. National policy, juridical system, etc. are the key elements in the successful implementation of regional policy. Problems of differences in regions can be solved by application of three approaches. The first approach is based on the strengths of free market economy. The second approach is based on effective and appropriate use of the means of regional development. The third approach seeks to stimulate the growth in every sphere of country’s economy where the competitive conditions are maintained. The evaluation of implementation of regional policy could be evaluated after several years, when means and instruments of the regional policy will be realized and it becomes possible evaluating their influence effect.